Educating the Muslims of America - Haddad, Yvonne Yazbeck, 1935-; Senzai, Farid; Smith, Jane I. (New York ; Oxford : Oxford University Press, 2009)
The essays collected in this volume look behind the walls of Islamic schools in America, discovering efforts to provide excellent instruction following national educational standards and attempts to inculcate Islamic values and protect students from the percieved dangers of secularism and the compromising values of American culture.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Islamic education -- United States; Islamic education -- Canada